Influences and Individualities: - Mohammad Shafiqul Islam (Crossings, 2020)
Nissim Ezekiel, recognized as the pioneering figure of Indian poetry in English, was influenced by a great many poets of the western literary tradition, subsequently influencing numerous poets of his succeeding generations. Having brought modernity into the literary scene of the Indian subcontinent, he made an immense contribution to English writing, initiating a new poetic trend in this region. Before him, Indian poetry had been charged with high romantic and mystic ideals, but he first began to present everyday life in poetry, abandoning the past trend. Well informed of the western tradition of the twentieth-century poetry, Ezekiel brought something new to Indian poetry in English. In his formative years, several poetic voices of the west and their works made an impact on his work, but like great poets of the world, he was able to set a new trend, create an individual style, and become influential to later generations of poets in India and beyond. This paper, therefore, explores how western tradition of modern and romantic poetry contributed to the shaping of Ezekiel’s poetic world. The paper also argues that Ezekiel’s arrival in the realm of Indian poetry in English gives birth to a new era of poetic tradition in India in particular and the whole subcontinent in general.